Green reduction of graphene oxide using Indian gooseberry (amla) extract for gas sensing applications. Issue 2 (April 2020) - Mascarenhas, Fiona Crystal; Sykam, Nagaraju; Selvakumar, M.; Mahesha, M G
Graphical abstract: Highlights: Synthesized rGO using Indian gooseberry (Amla) extract as green reducing agent. XPS, Raman, FTIR and UV–vis spectroscopy have confirmed the reduction of GO to rGO. Demonstrated application of rGO in ammonia gas detection using chemiresistor. Abstract: Graphene preparation from reduction of graphene oxide (GO) which is known as reduced graphene oxide (rGO) is considered as one of the promising methods for the development of graphene-based devices on a large scale at low-cost. In the present work, rGO has been successfully prepared using Indian gooseberry (Amla) extract, a green reducing agent, and its sensitivity for ammonia gas molecules has been studied using chemiresistor configuration. About 5 % sensitivity was observed for 3 ppm concentration of ammonia gas. Raman and X-ray photoelectron spectroscopy (XPS) spectra have confirmed the formation of rGO. Fourier transform infrared spectroscopy (FTIR), ultraviolet visible (UV–vis) spectroscopy and electron microscopy have been adopted for evaluating the quality of synthesized rGO. In addition, the green synthesized rGO has been evaluated for the device suitability by comparing its quality and performance with rGO synthesized using chemical reducing agent (hydrazine hydrate).